Constructing Treason, Narrating Truth: The 1794 Treason Trial of Thomas Holcroft and the Fate of English Jacobinism - Wallace, Miriam (Romanticism on the Net, 2007)
AbstractIn 1794, Britain experienced a public crisis in representation when twelve men were tried for “Constructive Treason” based upon their agitation for Parliamentary reform. The British nation is “constituted” by the conjunction of king and both houses of Parliament rather than by an originary document: under “constructive treason” an attack on one part of this “Happy Constitution” (Parliament) can be metonymically construed as an attack on another part (the monarchy or simply the dignity of the king himself). This essay takes the trial for High Treason of twelve radical reformers as its subject, with special attention to the inclusion of autodidact and radical author Thomas Holcroft among the accused. Rather than reading a literary text for its hidden political content, this essay instead reads public documents surrounding the trial for their figurative turn and as the sign of an emergent cultural debate over the relation of language to meaning with material and literary implications. Although the 1794 London Treason trials ended in acquittals or in dismissal of the charges, their impact upon the accused, and more broadly upon the project of the radical novel of purpose, was significant. Because the charge of constructive treason was successfully undercut by the radicals’ accusations that this was an overly-imaginative projection by the government, the English Jacobin novelists’ own project of enlisting active political imaginings through fictions was also made suspect. On the one hand, post-1795 the government and loyalists turned away from direct legal confrontations and toward the powers of imaginative literature in their future efforts to deauthorize the project of radical reform. On the other, the radicals’ success in tainting the government’s charges as overly speculative reflected back upon the Jacobin’s own projections and designs. Finally, the public discourse and documents surrounding the 1794 Treason Trials themselves are an important moment in the collision of the material with the imaginative at the turn of the century. The case of the 1794 Treason Trials and their implications for Jacobin fictions suggest particular benefits to the study of a broad range of materials beyond the usual parameters of “literature” as more than contextual documents.